2016
DOI: 10.7249/rr1539
|View full text |Cite
|
Sign up to set email alerts
|

Counterterrorism and Counterinsurgency in Somalia: Assessing the Campaign Against Al Shabaab

Abstract: This document and trademark(s) contained herein are protected by law. This representation of RAND intellectual property is provided for noncommercial use only. Unauthorized posting of this publication online is prohibited. Permission is given to duplicate this document for personal use only, as long as it is unaltered and complete. Permission is required from RAND to reproduce, or reuse in another form, any of its research documents for commercial use. For information on reprint and linking permissions, please… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…As former national security adviser Brent Scowcroft put it, "This world is not as dangerous as that during the Cold War, but it is much more complicated." 20 In such a complex and dynamic environment, strategic surprises may or may not occur more frequently than in decades past-this is unknowable. But we can safely assume that surprises will happen.…”
Section: Percentage Of Responsesmentioning
confidence: 99%
See 4 more Smart Citations
“…As former national security adviser Brent Scowcroft put it, "This world is not as dangerous as that during the Cold War, but it is much more complicated." 20 In such a complex and dynamic environment, strategic surprises may or may not occur more frequently than in decades past-this is unknowable. But we can safely assume that surprises will happen.…”
Section: Percentage Of Responsesmentioning
confidence: 99%
“…One widely accepted analysis has found that a 1-percent increase in trade relative to GDP leads to growth of per-capita GDP of between 0.85 percent and 1.97 percent. 20 A 2005 study pegged the value of trade to the U.S. economy on the order of $1 trillion, the equivalent of a gain in income of $2,800 to $5,000 each year for the average person in 2003 dollars. 21 U.S. corporations, in particular, reaped the benefits of the new global economy, as did high-skilled workers.…”
Section: An Interconnected Worldmentioning
confidence: 99%
See 3 more Smart Citations